Navigating uncertainty: the ripple effect of US economic policy on Chinese enterprise innovation - Gang Chen; Tajul Ariffin Masron; Diyanghuan Fan; Dansha Zhang (Cogent Economics & Finance)
This study explores the potential impact of US Economic Policy Uncertainty on the innovation activities of Chinese firms from 2010 to 2022. Based on the pooled data from the Shanghai and Shenzhen stock exchanges, a Generalized Method of Moments (GMM) approach was considered by the research to examine the impact of USEPU on innovation. The GMM approach provides unbiased estimates and allows policy evaluation under uncertainty. The results of the study found that USEPU has a significant negative effect on firm innovation. This indicates that even in a rapidly developing and highly integrated economy like China, external policy uncertainties can limit innovation activity. Moreover, it was also found that Firm size and return on assets (ROA) show a positive relationship with innovation. The 2-digit market share also indicated a positive impact on innovation. Finally, it was also recognized that leverage did not have a significant impact on firm innovation. The overall findings can be used to improve the policy-making process in order to reduce the negative impact of economic policy uncertainty.